Arsenal the official biography : the compelling story of an amazing club - Stammers, Steve (Hamlyn, a division of Octopus Publishing Group Ltd, 2008)
On Christmas Day in 1886 a group of munitions workers met in a pub to discuss their future as a football team. They decided to call themselves Royal Arsenal. This book gives you the complete picture of how the Arsenal came to be North London's most successful side